Detecting the location of pain by transferring its sensation from a person to a another one by EM waves in BBI technology - Sepehri, Alireza; Rathebe, Phoka; Valverde, Raul; Fioranelli, Massimo; Shoorvazi, Somayyeh (Edelweiss Applied Science and Technology, 2025)
Patients in a coma are unable to express their problems, including pain. Therefore, it is necessary to examine their feelings, including pain and its location, in a reliable manner. This research presents a novel method for transmitting feelings and pain between two individuals through the exchange of waves. The method involves designing an antenna that captures the patient’s blood waves, amplifies them, and transmits them to the blood of a healthy person. This antenna is composed of materials such as copper, iron, magnetic generators, ionized liquids, and blood from animals like rabbits. Blood molecules, such as hemoglobin, which contain oxygen and iron, exchange information with cells and sensory stimuli, such as neurons, by receiving and emitting spin waves. These waves are then transmitted to biological antennas and the blood of the second person. Consequently, the healthy individual can perceive the patient’s pain and determine its location. Prior to the transfer process, the voltage at various points on the bodies of both the patient and the healthy person is analyzed and simulated using computer models.